A novel series of highly potent 2,6,9-trisubstituted purine cyclin-dependent kinase inhibitors - Gucký, Tomáš; Jorda, Radek; Zatloukal, Marek; Bazgier, Václav; Berka, Karel; Řezníčková, Eva; Béres, Tibor; Strnad, Miroslav; Kryštof, Vladimír (Journal of medicinal chemistry, 2013)
The inhibition of overactive CDKs during cancer remains an important strategy in cancer drug development. We synthesized and screened a novel series of 2-substituted-6-biarylmethylamino-9-cyclopentylpurine derivatives for improved CDK inhibitory activity and antiproliferative effects. One of the most potent compounds, 6b, exhibited strong cytotoxicity in the human melanoma cell line G361 that correlated with robust CDK1 and CDK2 inhibition and caspase activation. In silico modeling of 6b in the active site of CDK2 revealed a high interaction energy, which we believe is due to the 6-heterobiarylmethylamino substitution of the purine moiety.
Keywords: Adenine; Models, Molecular; Phosphorylation; retinoblastomový protein; Cyclopentanes; Drug Screening Assays, Antitumor; Retinoblastoma Protein; Humans; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; fosforylace; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; Computer Simulation; Antineoplastic Agents; cyklin-dependentní kinasa 2; Purines; lidé; molekulární modely; cyklopentany; apoptóza; proteinkinasa CDC2; CDC2 Protein Kinase; adenin; počítačová simulace; Methylamines; puriny; screeningové testy protinádorových léčiv; nádorové buněčné linie; protinádorové látky; Cyclin-Dependent Kinase 2; Cell Line, Tumor; methylaminy; Apoptosis